Anti-dust photovoltaic module and preparation method thereof
By setting a negative charge nanocoat at the preset depth of the photovoltaic front panel surface of the photovoltaic module, the problems of low cleaning efficiency, high maintenance cost and poor environmental adaptability in extreme environments are solved, and the effect of improving the self-cleaning ability and long-term operation efficiency of the photovoltaic module is achieved.
Patent Information
- Application Number
- CN202411855937.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing photovoltaic modules have low cleaning efficiency, high maintenance costs and poor environmental adaptability in extreme environments, resulting in reduced performance and shortened service life.
Negative charge nanocoat is uniformly arranged at the preset depth of the photovoltaic front panel surface. The coating is prepared by mixing nanohydrophobic SiO2 aerogel, nanocellulose, negative charge material and organic solvent. The negative charge material is N-doped SnO2 or Ti4+, V5+ doped MoO3 or WO3, and the negative charge center is introduced through laser or plasma etching technology.
It improves the self-cleaning capacity and long-term operation efficiency of photovoltaic modules, can effectively resist the adhesion of dust, adapt to various usage environments such as deserts, and reduces maintenance costs.
Smart Images

Figure CN119325304B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solar photovoltaic power generation technology, and in particular to an anti-dust deposition photovoltaic component and a preparation method thereof. Background Art
[0002] As a key component of solar photovoltaic power generation systems, the core function of photovoltaic modules is to directly convert sunlight into electrical energy. With the growth of global demand for sustainable energy and the improvement of environmental awareness, the photovoltaic industry has experienced significant technological progress and development in recent years, and the market application scope of high-efficiency photovoltaic module technology has also been continuously expanded. In addition to large-scale ground power stations, it is also commonly used in distributed rooftop systems, building-integrated photovoltaic systems and other scenarios.
[0003] Photovoltaic modules are mostly used for power generation in outdoor environments, including those working in extreme desert weather. However, dust and dirt easily accumulate on the surface of photovoltaic modules in such environments, and dust easily blocks the sunlight reaching the photovoltaic cells, resulting in reduced power generation of photovoltaic cells. Dust accumulation also easily causes local overheating of photovoltaic modules, namely the "hot spot effect", which further damages the performance of photovoltaic modules and shortens their service life. Therefore, keeping the surface of photovoltaic modules clean is crucial to ensure the efficient and stable operation of solar energy systems.
[0004] At present, the main methods for solving the dust accumulation problem of photovoltaic modules in the industry include but are not limited to:
[0005] Natural cleaning: use rain or wind to remove dust naturally; manual cleaning: regular cleaning by manual wiping; automated cleaning system cleaning: use automated equipment for cleaning; special coating cleaning: apply coatings with hydrophobic or self-cleaning properties; optimized and improved structure: improve the design of components to reduce dust accumulation; monitoring and maintenance: regularly monitor component status and perform necessary cleaning and maintenance; intelligent solutions: develop intelligent systems to automatically identify and clean dust.
[0006] However, most of these methods rely on frame optimization, super-hydrophobic coating design and manual cleaning. Although they solve the dust accumulation problem to a certain extent, they are still limited in effect, and still have problems such as low cleaning efficiency, high maintenance cost and poor environmental adaptability. Especially in high-temperature environments with strong winds and sand, the rapid accumulation of dust will have a significant impact on the performance of photovoltaic modules. Summary of the invention
[0007] The purpose of the present application is to provide a dust-proof photovoltaic module and a preparation method thereof, so as to solve the technical problems of low cleaning efficiency, high maintenance cost and poor environmental adaptability of existing photovoltaic modules.
[0008] In a first aspect, the present application provides an anti-dust accumulation photovoltaic module, comprising:
[0009] A photovoltaic front panel, and a negatively charged nano-coating uniformly disposed at a preset depth below the surface of the photovoltaic front panel, wherein the preset depth is a first preset depth or a second preset depth, wherein the first preset depth is 5 to 15 μm, and the second preset depth is 1 to 100 nm;
[0010] The negatively charged nano coating is prepared by mixing nano hydrophobic SiO2 aerogel, nano cellulose, negatively charged material and organic solvent, wherein the negatively charged material is N-doped SnO2 or Ti 4+ 、V 5+ Doped MoO3 or WO3.
[0011] Furthermore, the anti-dust photovoltaic assembly further includes:
[0012] A first M-shaped coherently arranged structural layer formed on the surface of the photovoltaic front panel is formed by orderly arranging a plurality of groups of hill-like aggregated structures that are gradually raised from the periphery to the center;
[0013] The first M-type coherently arranged structural layer is formed by mixing SiO2 hydrophobic nanoparticles and an organic solvent, and adding a surfactant or a polymer as an additive.
[0014] Furthermore, the height of the highest point of the protrusions of each of the hill-like aggregation structures is 1-3 μm; and / or
[0015] The preset depth is a first preset depth.
[0016] Furthermore, the surface of the photovoltaic front panel is microstructured to form a second M-shaped coherently arranged structure surface, which is formed by a first wavy microstructure surface with concave and convex surfaces alternately arranged along a first direction and a second wavy microstructure surface with concave and convex surfaces alternately arranged along a second direction, and the first direction is perpendicular to the second direction;
[0017] The negatively charged nanocoating is uniformly etched at a second preset depth on the surface of the second M-type continuously arranged structure. The shape of the negatively charged nanocoating is consistent with the shape of the surface of the second M-type continuously arranged structure. The negatively charged nanocoating is an M-type continuously arranged negatively charged nanocoating.
[0018] Furthermore, the thickness of the negatively charged nano-coating is 300-500 nm; and / or
[0019] The distance between the lowest points of two adjacent concave surfaces of the first wavy microstructure surface and / or the second wavy microstructure surface is 5-10 μm, the depth of each concave surface is 1-3 μm, and there is a smooth transition between the concave surface and the convex surface.
[0020] In a second aspect, the present application provides a method for preparing a dust-proof photovoltaic module, comprising:
[0021] Step 100, preparing a negatively charged nano-coating, comprises:
[0022] Step 110, preparing materials for negatively charged nano-coating, including 5g of nano-hydrophobic SiO2 aerogel, 2g of nano-cellulose, negatively charged materials and 90-200mL of organic solvent, wherein the organic solvent is any one or more of ethanol, toluene and acetone, and the negatively charged material is 1g of N-doped SnO2, or 0.5g of Ti 4+ 、V 5+ Doped MoO3 or WO3;
[0023] Step 120, mixing preparation, is divided into two steps according to the selected negatively charged materials, including:
[0024] Step 121, if the negatively charged material is N-doped SnO2, ALD atomic layer vapor deposition is used, the gas in the vacuum chamber uses a nitrogen-containing gas source, and the negative charge content of the negatively charged center is adjusted by adjusting the nitrogen content of the deposited negatively charged material; or
[0025] Step 122, if the negatively charged material is Ti 4+ 、V 5+ The doped MoO3 or WO3 is evenly dispersed in an organic solvent using a high-speed disperser, and the coating is applied by solution coating after all components are fully dispersed;
[0026] Step 130, drying in an oven at 80°C for 24 hours until a uniform layer of solid powder is obtained on the photovoltaic front panel, which is the negatively charged nano coating;
[0027] Step 200, the negatively charged nano-coating obtained in step 100 is laser-introduced into the surface of the photovoltaic front panel at a preset depth by using SE laser technology.
[0028] Furthermore, the step 200 includes:
[0029] Step 210, first use SE laser technology to pre-coat the negatively charged nano-coating on the photovoltaic front panel;
[0030] Step 220, setting the laser power to 10W~100W, the scanning speed to 10mm / s, the repetition frequency to 50kHz, the energy density to 1J / cm², the pulse width to 10ns, and adjusting the laser focusing depth so that the negatively charged nano-coating is introduced to a preset depth on the surface of the photovoltaic front panel, the preset depth being a first preset depth, and the first preset depth being 5~15μm.
[0031] Furthermore, the method for preparing the anti-dust deposition photovoltaic module further comprises, after step 200, step 300 of controlling the self-assembly of the first M-shaped coherently arranged structural layer, including:
[0032] Step 310, preparation of a hydrophobic nano solution, first preparing 0.5wt% SiO2 hydrophobic nanoparticles and an organic solvent, and adding a surfactant or a polymer as an additive, wherein the surfactant is 0.1wt% sodium dodecyl sulfate, the polymer is 0.5wt% polyvinyl alcohol, and the organic solvent is ethanol, and then using a magnetic stirrer to stir the mixture to obtain a hydrophobic nano solution;
[0033] Step 320, self-assembly, first spray the hydrophobic nano solution evenly on the surface of the photovoltaic front panel by spraying, and then dry it naturally at room temperature, so that the hydrophobic nano solution solidifies and automatically curls to form the first stable M-shaped coherent arrangement structure layer.
[0034] Furthermore, in the method for preparing the anti-dust photovoltaic module, in step 320, spraying is performed using a spraying device, the spraying device uses a spray gun or an atomizer, the spraying pressure is set to 2-3 bar, the distance between the nozzle and the surface of the photovoltaic front panel is kept between 15-20 cm, and the spraying is performed evenly, and the spraying path and speed are adjusted according to the size of the photovoltaic front panel to cover the entire surface of the photovoltaic front panel;
[0035] During the spraying and curing process, ensure that the temperature is 20~25°C and the relative humidity is less than 50%. A constant temperature and humidity chamber can be used to control the environmental conditions.
[0036] Furthermore, the method for preparing the anti-dust photovoltaic module further includes an effect verification step, including:
[0037] Step 140 after step 130 includes step 141, analyzing the crystal structure of the solid powder in step 130 by X-ray diffraction to confirm the composition of the powder; step 142, observing the particle morphology and size distribution of the solid powder by using a scanning electron microscope; step 143, measuring the charge state of the surface of the powder particles by a Zeta potential analyzer to confirm that the surface of the solid powder is negatively charged; and / or
[0038] Step 230 after step 220 includes step 231, using an atomic force microscope to observe the surface of the treated photovoltaic front panel to confirm that the negative charge center is introduced into a preset depth; step 232, analyzing the surface of the treated photovoltaic front panel by X-ray photoelectron spectroscopy to verify the existence of the negative charge center; step 233, using a Zeta potential analyzer to measure the surface charge state of the treated photovoltaic front panel to confirm that the surface presents a stable negative charge; and / or
[0039] Step 330 after step 320 includes step 331, observing the formed first M-type coherently arranged structure layer using a scanning electron microscope; step 332, measuring the hydrophobicity of the first M-type coherently arranged structure layer using a contact angle meter. If the contact angle is greater than 90°, it indicates that the hydrophobicity of the first M-type coherently arranged structure layer is good.
[0040] In a third aspect, the present application provides another method for preparing a dust-proof photovoltaic module, comprising:
[0041] Step A, pre-treating the surface of the photovoltaic front panel and micro-structuring it to form a second M-type coherently arranged structure surface, comprising:
[0042] Step A1, forming a first wavy microstructure surface with concave and convex surfaces alternately arranged along a first direction, using laser micromachining technology to process the surface of the photovoltaic front panel, arranging multiple laser punching points evenly spaced along the first direction on the surface of the photovoltaic front panel, the spacing between two laser punching points is controlled to be 5~10μm, the punching depth of each laser punching point is controlled to be 1~3μm, and setting the laser power to 15W, the scanning speed to 20mm / s, the repetition frequency to 100kHz, and the energy density to 2J / cm², to obtain the first wavy microstructure surface;
[0043] Step A2, on the first wavy microstructure surface, change the laser running path to a laser running path perpendicular to the running direction of the laser running path in step A1, repeat step A1, adjust the laser power, the depth is consistent with step A1, on the basis of the first wavy microstructure surface, superimpose the second wavy microstructure surface with alternating concave and convex surfaces arranged along the second direction perpendicular to the first direction, and after smooth round convex points, form the second M-type coherently arranged structure surface.
[0044] Furthermore, the method for preparing the anti-dust photovoltaic module further includes:
[0045] Step B, preparing a negatively charged nano-coating, comprises:
[0046] Step B1, preparing a negatively charged nano-coating material, including 5% of nano-hydrophobic SiO2 aerogel, 2% of nano-cellulose, a negatively charged material and an organic solvent, wherein the negatively charged material is 1% of N-doped SnO2, or 0.5% of Ti 4+ 、V 5+ Doped MoO3 or WO3;
[0047] Step B2, a deposition process, using any one of physical vapor deposition, chemical vapor deposition and plasma vapor deposition techniques to deposit the negatively charged nano-coating material in step B1 on the surface of the photovoltaic front panel treated in step A, controlling the deposition rate to be 0.5 nm / s, and the total deposition time to be 20 minutes, to obtain a conformally deposited negatively charged nano-coating on the surface of the second M-type coherent arrangement structure of the photovoltaic front panel;
[0048] If N-doped SnO2 is used as the negatively charged material, the deposition process can also adopt ALD atomic layer vapor deposition, replace the gas in the vacuum chamber with a nitrogen-containing gas source, and adjust the negative charge content by adjusting the nitrogen content of the deposited negatively charged material.
[0049] Furthermore, the method for preparing the anti-dust photovoltaic module further includes:
[0050] Step C, driving the negatively charged nano-coating deposited in step B into the second preset depth on the surface of the second M-shaped coherent arrangement structure of the treated photovoltaic front panel by SE laser technology or plasma etching technology, comprising:
[0051] Step C1: If SE laser technology is used, set the laser power to 10W, the scanning speed to 10mm / s, the repetition frequency to 50kHz, and the energy density to 1J / cm²; or
[0052] Step C2: if plasma etching technology is used, argon is used as the working gas, the power is 50 W, and the etching time is 10 minutes.
[0053] Furthermore, the method for preparing the anti-dust photovoltaic module further includes an effect verification step, including:
[0054] Step A3 after step A2 includes step A31, using a scanning electron microscope to observe the microstructure of the cross section of the photovoltaic front panel to confirm that the surface forms the expected second M-type coherent arrangement structure surface; step A32, using a contact angle meter to measure the contact angle of the photovoltaic front panel surface before and after the treatment to confirm that the increase in surface roughness leads to an increase in the contact angle, indicating that the surface hydrophilicity is reduced; and / or
[0055] Step B3 after step B2 includes step B31, measuring the thickness of the negatively charged nano-coating by ellipsometry to confirm that the thickness of the negatively charged nano-coating is uniform and the thickness of the negatively charged nano-coating is 300-500 nm; step B32, analyzing the surface of the deposited negatively charged nano-coating by X-ray photoelectron spectroscopy to verify that the coating contains the expected components; and / or
[0056] Step C3 after step C1 or step C2 includes step C31, using a scanning electron microscope to observe the microstructural changes on the surface of the negatively charged nanocoating to confirm that the negatively charged particles are embedded in the surface of the second M-type coherently arranged structure; step C32, analyzing the surface of the negatively charged nanocoating after treatment by X-ray photoelectron spectroscopy to verify the existence of negative charge centers; step C33, using a Zeta potential analyzer to measure the charge state of the surface of the negatively charged nanocoating after treatment to confirm that the surface presents a stable negative charge.
[0057] Compared with the prior art, the anti-dust photovoltaic module and its preparation method provided by the present application uniformly arrange a negatively charged nano-coating at a preset depth on the surface of the photovoltaic front panel, and the negatively charged nano-coating is prepared by mixing nano-hydrophobic SiO2 aerogel, nano-cellulose, negatively charged material and organic solvent, and the negatively charged material is N-doped SnO2, or Ti 4+ and V 5+ The doped MoO3 or WO3, the negatively charged nano coating is used to penetrate its negatively charged material into the preset depth of the photovoltaic front panel surface through laser or plasma etching technology, and evenly forms a negatively charged nano coating with electrostatic repulsion function, which can generate a stable charge with the same electrostatic polarity as the dust particles on the photovoltaic front panel surface. The negatively charged material of the negatively charged nano coating is used as a negative charge source. Since the doped transition metal ions have unfilled d orbitals, they can change the charge state of the material by accepting or donating electrons, and can change the energy band structure of the doped material, introduce new energy levels or change the original energy level position, thereby forming a negative charge center on the material surface. The surface of the negatively charged nano coating has a negative charge, and the dust particles also usually have a negative charge. The principle of electrostatic mutual repulsion is used to effectively resist the adhesion of dust, thereby improving the self-cleaning ability and long-term operation efficiency of the photovoltaic module. In addition, this anti-dust photovoltaic module can adapt to various use environments such as deserts to solve the technical problems of low cleaning efficiency, high maintenance cost and poor environmental adaptability of existing photovoltaic modules. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0059] Figure 1 A schematic diagram of the electrostatic repulsion principle of the photovoltaic front panel surface provided in an embodiment of the present application;
[0060] Figure 2 A schematic diagram of the structure of the first M-type coherently arranged structural layer provided in the first embodiment of the present application Figure 1 ;
[0061] Figure 3 A schematic diagram of the structure of the first M-type coherently arranged structural layer provided in the first embodiment of the present application Figure 2 ;
[0062] Figure 4 A schematic diagram of the microstructure of a photovoltaic front panel provided in the first embodiment of the present application;
[0063] Figure 5 A schematic diagram of the microstructure of a photovoltaic front panel provided in the second embodiment of the present application;
[0064] Figure 6 A schematic structural diagram of a first wavy microstructure surface of a photovoltaic front plate provided in a second embodiment of the present application;
[0065] Figure 7 This is a schematic structural diagram of a second M-type coherently arranged structural surface of a photovoltaic front panel provided in the second embodiment of the present application.
[0066] Reference numerals:
[0067] 100-anti-dust photovoltaic modules;
[0068] 10- Photovoltaic front panel;
[0069] 11- photovoltaic front panel surface;
[0070] 12- original surface;
[0071] 13-first wave-shaped microstructure surface;
[0072] 131-concave;
[0073] 1311- lowest point of concave surface;
[0074] 132-convex;
[0075] 14- The second M-type coherently arranged structure surface;
[0076] 20-the first M-type coherently arranged structural layer;
[0077] 21-Hill-like aggregate structure;
[0078] 211-highest point of the bulge;
[0079] 31-a first negatively charged nano coating;
[0080] 32-a second negatively charged nano coating;
[0081] 40-Laser penetration point;
[0082] 50- Dust particles with negative charge. DETAILED DESCRIPTION
[0083] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0084] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0085] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0086] In the description of the present application, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the product of the application is usually placed when in use. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0087] In addition, the terms "horizontal", "vertical", "overhanging" and the like do not mean that the components are required to be absolutely horizontal or overhanging, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0088] In the description of this application, it should also be noted that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0089] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0090] like Figures 1 to 6 As shown, an embodiment of the present application provides an anti-dust deposition photovoltaic module 100 and a method for preparing the anti-dust deposition photovoltaic module 100, comprising a photovoltaic front panel 10, and a negatively charged nano-coating uniformly arranged at a preset depth on the surface of the photovoltaic front panel 10, the negatively charged nano-coating being prepared by mixing nano-hydrophobic SiO2 aerogel, nano-cellulose, a negatively charged material and an organic solvent, the negatively charged material being N-doped SnO2, or Ti4+, V5+-doped MoO3 or WO3.
[0091] Compared with the prior art, the anti-dust deposition photovoltaic module 100 and its preparation method provided in the embodiment of the present application uniformly arranges a negatively charged nano-coating at a preset depth on the surface of the photovoltaic front panel 10, and the negatively charged nano-coating is prepared by mixing nano-hydrophobic SiO2 aerogel, nano-cellulose, negatively charged materials and organic solvents. The negatively charged materials are N-doped SnO2, or Ti4+ and V5+-doped MoO3 or WO3. The negatively charged nano-coating is etched by laser or plasma etching technology to penetrate the negatively charged materials into the preset depth on the surface of the photovoltaic front panel 10, and uniformly forms a negatively charged nano-coating with electrostatic repulsion function. The nano coating can generate a stable charge with the same electrostatic polarity as the dust particles on the surface of the photovoltaic front panel 10. The negatively charged material of the negatively charged nano coating serves as a negative charge source. Since the doped transition metal ions have unfilled d orbitals, they can change the charge state of the material by accepting or donating electrons, and can change the energy band structure of the doped material, introduce new energy levels or change the original energy level positions, thereby forming a negative charge center on the surface of the material. The surface of the negatively charged nano coating carries a negative charge, and the dust particles also usually carry a negative charge. The electrostatic mutual repulsion principle is used to effectively resist the attachment of dust, such as Figure 1 The negatively charged dust particles 50 are shown. Figure 1 The figure shows the electrostatic repulsion principle diagram of the photovoltaic front panel surface, where F is the electrostatic repulsion force, thereby improving the self-cleaning ability and long-term operating efficiency of the photovoltaic module. In addition, this anti-dust photovoltaic module 100 can adapt to various usage environments such as deserts to solve the technical problems of low cleaning efficiency, high maintenance cost and poor environmental adaptability of existing photovoltaic modules.
[0092] First, as Figures 2 to 4As shown, the first embodiment of the present application provides an anti-dust photovoltaic assembly 100, including a photovoltaic front panel 10, and a first negatively charged nano-coating 31 uniformly arranged at a first preset depth D1 on the surface 11 of the photovoltaic front panel. The first negatively charged nano-coating 31 is uniformly arranged, preferably a planar fiber film structure. The first negatively charged nano-coating 31 is made of the same material as the aforementioned negatively charged nano-coating, and is prepared by mixing nano-hydrophobic SiO2 aerogel, nano-cellulose, negatively charged materials and organic solvents. The negatively charged materials are N-doped SnO2, or Ti4+, V5+ doped MoO3 or WO3. Preferably, the first preset depth D1 is 5~15μm, ensuring that the negatively charged material is introduced into the photovoltaic front panel surface at a depth of 5~15μm, ensuring the effectiveness of the use of the specific structure.
[0093] The setting of the first negatively charged nano-coating 31 can improve the self-cleaning ability and long-term operation efficiency of the anti-dust deposition photovoltaic module 100. Through the uniform adhesion of the functional nano-materials of the first negatively charged nano-coating 31, it is ensured that the first negatively charged nano-coating 31 can generate the same stable charge as the dust particles on the photovoltaic front panel surface 11, and ensure that the reverse charge generated by the first negatively charged nano-coating 31 on the photovoltaic front panel surface 11 is stable and reliable, thereby enhancing the performance of the anti-dust deposition coating, improving the power generation efficiency of the photovoltaic module, and increasing the economic benefits.
[0094] Further, such as Figure 2 and Figure 3 As shown, the anti-dust photovoltaic assembly 100 provided in the first embodiment also includes a first M-type coherently arranged structural layer 20 formed on the photovoltaic front panel surface 11, and the first M-type coherently arranged structural layer 20 is formed by orderly arranging a plurality of groups of hill-like aggregate structures 21 that are gradually raised from the periphery to the center; the first M-type coherently arranged structural layer 20 is formed by mixing SiO2 hydrophobic nanoparticles and an organic solvent, and adding a surfactant or a polymer as an additive, wherein the surfactant can be sodium dodecyl sulfate (SDS), the polymer can be polyvinyl alcohol (PVA), and the organic solvent can be ethanol; the specific preparation method of the first M-type coherently arranged structural layer 20 is described in detail below. It is preferred that the height of the highest point 211 of the convexity of each hill-like aggregate structure 21 of the first M-type coherently arranged structural layer 20 is 1-3 μm.
[0095] Regarding the formation of the first M-type coherently arranged structure layer 20 formed by the orderly arrangement of multiple groups of hill-like aggregation structures 21 that gather from the periphery to the center and gradually bulge, the principle is that SiO2 hydrophobic nanoparticles are affected by surface tension and tend to minimize their surface area, so they will automatically arrange into an ordered structure during the solidification process; and, at the nanoscale, capillary forces can significantly affect the arrangement of particles, especially during the evaporation of the solution, the capillary effect will cause the particles to aggregate along a specific direction to form a coherent structure; and, the van der Waals force, electrostatic force and other short-range attractions between particles also contribute to the aggregation of particles to form an ordered structure.
[0096] On the basis of providing the first negatively charged nano-coating layer 31 , a first M-type coherently arranged structural layer 20 is also formed on the photovoltaic front panel surface 11 to further effectively resist the adhesion of dust.
[0097] The innovative inspiration of the first M-type coherently arranged structural layer 20 comes from the structure of the surface of penguin feathers. The wings of penguins are covered with tiny, continuous barbs at the microstructure level. These barbs form a dense, water-proof fiber network. There are also tiny wrinkles on the surface of these barbs. These spaces will lock the air and reduce the contact area between the feathers and small water droplets, making it difficult for water droplets to adhere to the feather surface. Based on this, it is proposed to set the above-mentioned first M-type coherently arranged structural layer 20 on the surface of the photovoltaic front panel 11, and combine the negatively charged nano-coating of the fiber film structure mentioned above, and use electrostatic action to combine with the air layer to make the water droplets stay on the surface of the photovoltaic front panel 11 in a spherical shape, and the dust is repelled from the surface of the photovoltaic front panel 11, which significantly improves the self-cleaning ability of the photovoltaic front panel surface, and can effectively reduce dust accumulation even in dry or windy areas.
[0098] Second, as Figures 5 to 7 As shown, the second embodiment of the present application provides another anti-dust deposition photovoltaic assembly 100, including a photovoltaic front panel 10, the surface of which is microstructured to form a second M-type coherently arranged structure surface 14, which is formed by superimposing and smoothing a first wavy microstructure surface 13 with concave and convex surfaces alternately arranged along a first direction X and a second wavy microstructure surface with concave and convex surfaces alternately arranged along a second direction Y. Figure 6 and Figure 7 The first direction X and the second direction Y shown are perpendicular to each other. Figure 5 and Figure 6 As shown, the original surface 12 is first processed into a first wavy microstructure surface 13, and then a second wavy microstructure surface is superimposed on the first wavy microstructure surface 13 to form a Figure 7The second M-type coherently arranged structure surface 14 is shown, and a negatively charged nano-coating is uniformly etched at a second preset depth D2 of the second M-type coherently arranged structure surface 14. The negatively charged nano-coating is a second negatively charged nano-coating 32. The shape trend of the second negatively charged nano-coating 32 is consistent with the shape trend of the second M-type coherently arranged structure surface 14, and is an M-type coherently arranged negatively charged nano-coating; the second negatively charged nano-coating 32 also preferably adopts a fiber film structure. The second negatively charged nano-coating 32 is made of the same material as the aforementioned negatively charged nano-coating, and is prepared by mixing nano-hydrophobic SiO2 aerogel, nano-cellulose, negatively charged materials and organic solvents. The negatively charged material is N-doped SnO2, or Ti4+, V5+-doped MoO3 or WO3.
[0099] The anti-dust deposition photovoltaic assembly 100 provided by the second embodiment directly processes the surface of the photovoltaic front panel 10 into a second M-type continuously arranged structural surface 14, thereby increasing the specific surface area of the surface of the photovoltaic front panel 10 in contact with the outside world, and uniformly etches a second negatively charged nano-coating 32 consistent with its shape at a second preset depth D2 of the second M-type continuously arranged structural surface 14, thereby also maximizing the specific surface area of the second negatively charged nano-coating 32, thereby improving the electrostatic repulsion and dust blocking capabilities of the surface of the photovoltaic front panel 10, and further improving the self-cleaning capability and long-term operating efficiency of the surface of the photovoltaic front panel 10.
[0100] Further specifically, the second preset depth D2 is preferably 1~100nm to ensure the effectiveness of the use of the specific structure; the thickness of the second negatively charged nano-coating 32 is preferably 300~500nm; the spacing between the lowest points 1311 of two adjacent concave surfaces of the first wavy microstructure surface 13 is preferably 5~10μm, and the depth of each concave surface 131 is 1~3μm; the spacing between the lowest points 1311 of two adjacent concave surfaces of the second wavy microstructure surface is preferably 5~10μm, and the depth of each concave surface 131 is 1~3μm; and a smooth transition is preferably provided between each concave surface 131 and each convex surface 132.
[0101] In a third aspect, the present application further provides a method for preparing the anti-dust photovoltaic module 100 of the first embodiment, which may specifically include:
[0102] Step 100, preparing a negatively charged nano-coating, namely, a first negatively charged nano-coating 31, comprises:
[0103] Step 110, preparing materials for the negatively charged nano-coating (i.e., the first negatively charged nano-coating 31), including: nano-hydrophobic SiO2 aerogel (5 g), nano-cellulose (2 g), negatively charged materials, and organic solvents (90-200 mL). The organic solvents can be any one or more of ethanol, toluene, and acetone, with an amount of 90-200 mL, and the concentration range is adjusted according to actual needs, preferably 90 mL. The negatively charged material is N-doped SnO2 (1 g), or Ti-doped 4+ 、V 5+ Doped MoO3 or WO3 (0.5 g)
[0104] Step 120, mixing and preparing, two steps are performed respectively according to the selected negatively charged materials, including:
[0105] Step 121, if the negative charge material is N-doped SnO2, ALD atomic layer vapor deposition is used, the gas in the vacuum chamber uses a nitrogen-containing gas source, and the negative charge content of the negative charge center is adjusted by adjusting the nitrogen content of the deposited negative charge material; or
[0106] Step 122, if the negatively charged material is Ti 4+ 、V 5+ The doped MoO3 or WO3 is uniformly dispersed in an organic solvent using a high-speed disperser, and after all components are fully dispersed, the coating is applied by a solution coating method, which can be specifically applied by a scraper or slit coating;
[0107] Then, after performing step 121 or step 122, perform step 130, drying in an oven at 80° C. for 24 hours until a uniform layer of solid powder is obtained on the photovoltaic front panel 10, namely, a negatively charged nano-coating (i.e., the first negatively charged nano-coating 31);
[0108] The method may further include step 140, an effect verification step, which can further confirm the formation and functional effectiveness of the negatively charged nano-coating, and may specifically include:
[0109] Step 141, analyzing the crystal structure of the solid powder in step 130 by X-ray diffraction (XRD) to confirm the composition of the powder;
[0110] Step 142, using a scanning electron microscope (SEM) to observe the morphology and size distribution of the solid powder particles;
[0111] Step 143, measuring the charge state of the surface of the powder particles by a Zeta potential analyzer to confirm that the surface of the solid powder is negatively charged.
[0112] Step 200, the negatively charged nano-coating obtained in step 100 is introduced into the surface of the photovoltaic front panel 10 at a preset depth by using SE laser technology to introduce a negative charge center; specifically, it may include:
[0113] Step 210, using SE laser technology to pre-coat a negatively charged nano-coating (i.e., a first negatively charged nano-coating 31) on the photovoltaic front panel 10;
[0114] Step 220, setting the laser power to 10W~100W, the scanning speed to 10mm / s, the repetition frequency to 50kHz, the energy density to 1J / cm², and the pulse width to 10ns;
[0115] Adjust the laser focusing depth so that the negatively charged nano-coating (i.e., the first negatively charged nano-coating 31) is introduced to a preset depth on the surface of the photovoltaic front panel, the preset depth being a first preset depth D1, and the first preset depth D1 being 5-15 μm;
[0116] The method may further include step 230, an effect verification step, which can further confirm whether the negative charge center is introduced into the preset depth, and the existence, charge state and stability of the negative charge center, which may specifically include:
[0117] Step 231 , using an atomic force microscope (AFM) to observe the surface of the photovoltaic front panel 10 after treatment, and confirming that the negative charge center is introduced into a preset depth;
[0118] Step 232 , analyzing the surface of the photovoltaic front panel 10 after treatment by X-ray photoelectron spectroscopy (XPS) to verify the existence of negative charge centers;
[0119] Step 233 , using a Zeta potential analyzer to measure the surface charge state of the photovoltaic front panel 10 after treatment, confirming that the surface presents a stable negative charge.
[0120] The preparation method of the anti-dust photovoltaic module 100 provided in the first embodiment of the present application introduces the prepared negatively charged nano-coating into the surface of the photovoltaic front panel by combining liquid coating, vacuum deposition and laser technology; and introduces the negatively charged nano-coating material into the interior of the photovoltaic front panel in a form as lossless as possible by limiting the laser type, power and speed, and introduces the negative charge center into the surface of the photovoltaic front panel, so that the photovoltaic front panel as a whole exhibits negative electrical properties; and uses nano-hydrophobic SiO2 aerogel + nano-cellulose + N-doped SnO2, or doped Ti 4 ⁺、V 5 ⁺ MoO3 or WO3, etc. These ions have strong redox ability and can form a stable negative charge center during laser processing. The negatively charged nano-coating material is injected into the surface of the glass or flexible photovoltaic front panel. The first preset depth D1 of the injection can be 5~15μm, so that the negative charge center can maintain negative charge stably and achieve long-term and stable self-cleaning of the photovoltaic front panel surface.
[0121] Furthermore, the method may further include step 300 of controlling the self-assembly of the first M-shaped coherently arranged structural layer 20, which may specifically include:
[0122] Step 310, preparation of a hydrophobic nano-solution, first accurately weigh 0.5 wt% of SiO2 hydrophobic nano-particles and mix them with an organic solvent, wherein the organic solvent may be ethanol;
[0123] Then, a surfactant or a polymer is added as an additive to enhance the surface tension and the capillary effect. The surfactant may be sodium dodecyl sulfate (SDS), and specifically, 0.1 wt% of sodium dodecyl sulfate (SDS) may be added. The polymer may be polyvinyl alcohol (PVA), and specifically, 0.5 wt% of polyvinyl alcohol (PVA) may be added.
[0124] Then, the mixture formed above can be stirred evenly using a magnetic stirrer to ensure that the nanoparticles are well dispersed in the solution to obtain a hydrophobic nano-solution with good hydrophobicity;
[0125] Step 320, self-assembly, first spraying the hydrophobic nano solution uniformly on the surface of the photovoltaic front panel 10 by spraying, and then drying it naturally at room temperature, or slightly heating it, preferably at a temperature range of 25-45° C., so that the hydrophobic nano solution solidifies and automatically curls to form a stable first M-shaped coherent arrangement structure layer 20; further specifically, it may include:
[0126] Spraying equipment and parameter settings: Spraying can be performed using a spray gun or atomizer; the spraying pressure is set to 2-3 bar to ensure uniform dispersion of the nanoparticle solution; the distance between the nozzle and the surface of the photovoltaic front panel 10 is kept between 15-20 cm to spray evenly to obtain a uniform coating; and the spraying path and speed are adjusted according to the size of the photovoltaic front panel 10 to ensure that the entire surface of the photovoltaic front panel 10 is covered;
[0127] Environmental condition control: During the spraying and curing process, ensure that the temperature is 20~25°C and the relative humidity is less than 50% to avoid the solution evaporating too quickly or too slowly. The environmental conditions can be controlled by a constant temperature and humidity chamber.
[0128] The mechanism principle of the self-assembly of the first M-type coherently arranged structural layer 20 is mainly determined by surface tension, capillary effect and interaction between particles. Specifically, with respect to surface tension, the nanoparticles in the solution will be affected by the surface tension and tend to minimize their surface area, so they will automatically arrange into an ordered structure during the solidification process; with respect to the capillary effect, at the nanoscale, the capillary force can significantly affect the arrangement of the particles, especially during the evaporation of the solution, the capillary effect will cause the particles to aggregate in a specific direction to form a coherent structure; with respect to interaction between particles, the van der Waals force, electrostatic force and other short-range attractions between particles also contribute to the aggregation of particles to form an ordered structure.
[0129] The method may further include step 330, an effect verification step, which can further confirm the hydrophobic performance of the first M-shaped coherently arranged structural layer 20, and may specifically include:
[0130] Step 331 , using a scanning electron microscope (SEM) to observe the formed first M-type coherently arranged structure layer 20 ;
[0131] Step 332 , measuring the hydrophobicity of the first M-type coherently arranged structure layer 20 by using a contact angle measuring instrument. If the contact angle is greater than 90°, it indicates that the hydrophobicity of the first M-type coherently arranged structure layer 20 is good.
[0132] By combining the material formula and coating process in the preparation method of step 300 of the present application, a stable first M-type coherently arranged structural layer 20 can be automatically formed on the surface of the photovoltaic front panel, and the self-organization and uniform distribution of the coating structure can be achieved without additional molding steps, simplifying the preparation process of the coating and improving production efficiency. In addition, the first M-type coherently arranged structural layer 20 formed on the surface of the photovoltaic front panel by balancing the surface tension and the capillary effect can further effectively resist the adhesion of dust, so that water droplets stay on the surface 11 of the photovoltaic front panel, and dust is excluded from the surface 11 of the photovoltaic front panel, which significantly improves the self-cleaning ability of the photovoltaic front panel surface, and can effectively reduce dust accumulation even in dry or windy areas.
[0133] In a fourth aspect, the present application further provides a method for preparing the anti-dust photovoltaic module 100 of the second embodiment, which may specifically include:
[0134] Step A, pre-treating the surface of the photovoltaic front panel 10 to microstructure it to form a second M-shaped coherently arranged structure surface 14, comprising:
[0135] Step A1, forming a first wavy microstructure surface 13 with concave and convex surfaces alternately arranged along a first direction X, using laser micromachining technology to process the surface of the photovoltaic front panel 10, and evenly arranging a plurality of laser punching points 40 along the first direction X on the surface of the photovoltaic front panel 10, the spacing between two laser punching points 40 is controlled to be 5-10 μm, the punching depth of each laser punching point 40 is controlled to be 1-3 μm, and the laser power is set to 15 W, the scanning speed is 20 mm / s, the repetition frequency is 100 kHz, and the energy density is 2 J / cm², so as to obtain the first wavy microstructure surface 13, as shown in FIG. Figure 5 and Figure 6 As shown;
[0136] Step A2, on the first wavy microstructure surface 13, change the laser running path to a laser running path perpendicular to the running direction of the laser running path in step A1, repeat step A1, adjust the laser power, the depth is consistent with step A1, and on the basis of the first wavy microstructure surface 13, superimpose a second wavy microstructure surface with alternating concave and convex surfaces arranged along a second direction Y perpendicular to the first direction X, and after smooth round convex point processing, form a second M-shaped coherently arranged structure surface 14.
[0137] Furthermore, step A3, an effect verification step, may be included to further confirm that the expected second M-shaped coherently arranged structure surface 14 is formed on the surface, and to confirm whether the hydrophobicity of the surface is improved, which may specifically include:
[0138] Step A31, using a scanning electron microscope (SEM) to observe the microstructure of the cross section of the photovoltaic front panel, and confirming that the surface forms the expected second M-type coherently arranged structure surface 14;
[0139] Step A32, measuring the contact angle of the photovoltaic front panel surface before and after the treatment by a contact angle meter, confirming that the increase in surface roughness leads to an increase in the contact angle, indicating that the surface hydrophilicity is reduced, that is, the surface hydrophobicity is improved.
[0140] Step B, preparing a negatively charged nano-coating, i.e., a second negatively charged nano-coating 32, comprises:
[0141] Step B1, preparing negative charge nano coating (i.e., second negative charge nano coating 32) materials, including: nano hydrophobic SiO2 aerogel (5%), nano cellulose (2%), negative charge materials and organic solvents, wherein the negative charge materials are N-doped SnO2 (1%) or Ti 4+ 、V 5+ Doped MoO3 or WO3 (0.5%), nano-hydrophobic SiO2 aerogel has good light transmittance and does not affect light capture as a coating material;
[0142] Step B2, deposition process, using any one of physical vapor deposition, chemical vapor deposition and plasma vapor deposition techniques to deposit the negatively charged nano-coating material in step B1 (i.e., the second negatively charged nano-coating 32) on the surface of the photovoltaic front panel treated in step A, controlling the deposition rate to be 0.5 nm / s, and the total deposition time to be 20 minutes, to obtain the second negatively charged nano-coating 32 conformally deposited on the second M-shaped coherently arranged structure surface 14 of the photovoltaic front panel;
[0143] If N-doped SnO2 is used as the negative charge material, the deposition process can also adopt ALD atomic layer vapor deposition, replace the gas in the vacuum chamber with a nitrogen-containing gas source, and adjust the negative charge content by adjusting the nitrogen content of the deposited negative charge material;
[0144] The method may further include step B3, an effect verification step, which may specifically include:
[0145] Step B31, using ellipsometry to measure the thickness of the second negatively charged nano-coating to confirm that the coating thickness is uniform and the coating thickness is 10-100 nm;
[0146] Step B32, analyzing the surface of the deposited negatively charged nano-coating by X-ray photoelectron spectroscopy (XPS) to verify that the coating contains the expected components.
[0147] Step C, using SE laser technology or plasma etching technology to drive the second negatively charged nano-coating 32 deposited in step B into the second M-shaped coherently arranged structure surface 14 of the treated photovoltaic front panel 10 at a second preset depth D2, wherein the second preset depth D2 is 1-100 nm. Figure 5 As shown; according to the different technologies used, it can be divided into two steps, namely:
[0148] Step C1: If SE laser technology is used, set the laser power to 10W, the scanning speed to 10mm / s, the repetition frequency to 50kHz, and the energy density to 1J / cm²; or
[0149] Step C2: if plasma etching technology is used, argon is used as the working gas, the power is 50 W, and the etching time is 10 minutes.
[0150] The method may further include step C3, an effect verification step, comprising:
[0151] Step C31, using a scanning electron microscope (SEM) to observe the microstructural changes on the surface of the second negatively charged nano-coating 32, and confirming that the negatively charged particles are embedded in the second M-type coherently arranged structure surface 14;
[0152] Step C32, analyzing the surface of the second negatively charged nano-coating 32 after treatment by X-ray photoelectron spectroscopy (XPS) to verify the existence of negative charge centers;
[0153] Step C33, using a Zeta potential analyzer to measure the surface charge state of the second negatively charged nano-coating 32 after treatment, confirming that the surface presents a stable negative charge.
[0154] The preparation method of the anti-dust photovoltaic component 100 provided in the second embodiment of the present application combines laser technology, plasma etching technology, etc., to directly process the surface of the photovoltaic front panel into a second M-shaped coherent arrangement structure surface 14, and inject the prepared second negatively charged nano-coating 32 into the second preset depth of the photovoltaic front panel surface, introduce the negative charge center into the second preset depth of the photovoltaic front panel surface, increase the specific surface area, and at the same time make the photovoltaic front panel as a whole present a stable negative charge performance, ensure that the second negatively charged nano-coating 32 maintains the same charge as the dust for a long time, and realizes long-term and stable dust prevention of the photovoltaic front panel surface.
[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A dust-proof photovoltaic module, characterized in that: include: A photovoltaic front panel, and a negatively charged nano-coating uniformly disposed at a preset depth below the surface of the photovoltaic front panel, wherein the preset depth is a first preset depth or a second preset depth, wherein the first preset depth is 5 to 15 μm, and the second preset depth is 1 to 100 nm; The negatively charged nano coating is prepared by mixing nano hydrophobic SiO2 aerogel, nano cellulose, negatively charged material and organic solvent, wherein the negatively charged material is N-doped SnO2 or Ti 4+ 、V 5+ Doped MoO3 or WO3.
2. The anti-dust photovoltaic module according to claim 1, characterized in that: Also includes: A first M-shaped coherently arranged structural layer formed on the surface of the photovoltaic front panel is formed by orderly arranging a plurality of groups of hill-like aggregated structures that are gradually raised from the periphery to the center; The first M-type coherently arranged structural layer is formed by mixing SiO2 hydrophobic nanoparticles and an organic solvent, and adding a surfactant or a polymer as an additive.
3. The anti-dust photovoltaic module according to claim 2, characterized in that: The height of the highest point of the protrusions of each hill-like aggregation structure is 1-3 μm; and / or The preset depth is a first preset depth.
4. The anti-dust photovoltaic module according to claim 1, characterized in that: The surface of the photovoltaic front plate is microstructured to form a second M-shaped coherently arranged structure surface, which is formed by a first wavy microstructure surface with concave and convex surfaces alternately arranged along a first direction and a second wavy microstructure surface with concave and convex surfaces alternately arranged along a second direction, and the first direction is perpendicular to the second direction; The negatively charged nanocoating is uniformly etched at a second preset depth below the surface of the second M-type continuously arranged structure. The shape of the negatively charged nanocoating is consistent with the shape of the surface of the second M-type continuously arranged structure. The negatively charged nanocoating is an M-type continuously arranged negatively charged nanocoating.
5. The anti-dust photovoltaic module according to claim 4, characterized in that: The thickness of the negatively charged nano coating is 300-500 nm; and / or The distance between the lowest points of two adjacent concave surfaces of the first wavy microstructure surface and / or the second wavy microstructure surface is 5-10 μm, the depth of each concave surface is 1-3 μm, and there is a smooth transition between the concave surface and the convex surface.
6. A method for preparing a dust-proof photovoltaic module according to any one of claims 1 to 3, characterized in that: include: Step 100, preparing a negatively charged nano-coating, comprises: Step 110, preparing materials for negatively charged nano-coating, including 5g of nano-hydrophobic SiO2 aerogel, 2g of nano-cellulose, negatively charged materials and 90-200mL of organic solvent, wherein the organic solvent is any one or more of ethanol, toluene and acetone, and the negatively charged material is 1g of N-doped SnO2, or 0.5g of Ti 4+ 、V 5+ Doped MoO3 or WO3; Step 120, mixing preparation, is divided into two steps according to the selected negatively charged materials, including: Step 121, if the negatively charged material is N-doped SnO2, ALD atomic layer vapor deposition is used, the gas in the vacuum chamber uses a nitrogen-containing gas source, and the negative charge content of the negatively charged center is adjusted by adjusting the nitrogen content of the deposited negatively charged material; or Step 122, if the negatively charged material is Ti 4+ 、V 5+ The doped MoO3 or WO3 is evenly dispersed in an organic solvent using a high-speed disperser, and the coating is applied by solution coating after all components are fully dispersed; Step 130, drying in an oven at 80°C for 24 hours until a uniform layer of solid powder is obtained on the photovoltaic front panel, which is the negatively charged nano coating; Step 200, introducing the negatively charged nano-coating obtained in step 100 into a preset depth on the surface of the photovoltaic front panel by using SE laser technology.
7. The method for preparing a dust-proof photovoltaic module according to claim 6, characterized in that: The step 200 comprises: Step 210, first use SE laser technology to pre-coat the negatively charged nano-coating on the photovoltaic front panel; Step 220, setting the laser power to 10W~100W, the scanning speed to 10mm / s, the repetition frequency to 50kHz, the energy density to 1J / cm², the pulse width to 10ns, and adjusting the laser focusing depth so that the negatively charged nano-coating is introduced to a preset depth on the surface of the photovoltaic front panel, wherein the preset depth is a first preset depth.
8. The method for preparing a dust-proof photovoltaic module according to claim 7, characterized in that: After step 200, the method further includes step 300 of controlling the self-assembly of the first M-shaped coherently arranged structural layer, including: Step 310, preparation of a hydrophobic nano solution, first preparing 0.5wt% SiO2 hydrophobic nanoparticles and an organic solvent, and adding a surfactant or a polymer as an additive, wherein the surfactant is 0.1wt% sodium dodecyl sulfate, the polymer is 0.5wt% polyvinyl alcohol, and the organic solvent is ethanol, and then using a magnetic stirrer to stir the mixture to obtain a hydrophobic nano solution; Step 320, self-assembly, first spray the hydrophobic nano solution evenly on the surface of the photovoltaic front panel by spraying, and then dry it naturally at room temperature, so that the hydrophobic nano solution solidifies and automatically curls to form the first stable M-shaped coherent arrangement structure layer.
9. The method for preparing a dust-proof photovoltaic module according to claim 8, characterized in that: In step 320, spraying is performed using a spraying device, wherein the spraying device uses a spray gun or an atomizer, the spraying pressure is set to 2-3 bar, the distance between the nozzle and the surface of the photovoltaic front panel is kept between 15-20 cm, and the spraying is performed evenly, and the spraying path and speed are adjusted according to the size of the photovoltaic front panel to cover the entire surface of the photovoltaic front panel; During the spraying and curing process, ensure that the temperature is 20~25°C and the relative humidity is less than 50%. A constant temperature and humidity chamber can be used to control the environmental conditions.
10. The method for preparing a dust-proof photovoltaic module according to claim 9, characterized in that: It also includes effect verification steps, including: Step 140 after step 130 includes step 141, analyzing the crystal structure of the solid powder in step 130 by X-ray diffraction to confirm the composition of the powder; step 142, observing the particle morphology and size distribution of the solid powder by using a scanning electron microscope; step 143, measuring the charge state of the surface of the powder particles by a Zeta potential analyzer to confirm that the surface of the solid powder is negatively charged; and / or Step 230 after step 220 includes step 231, using an atomic force microscope to observe the surface of the treated photovoltaic front panel to confirm that the negative charge center is introduced into a preset depth; step 232, analyzing the surface of the treated photovoltaic front panel by X-ray photoelectron spectroscopy to verify the existence of the negative charge center; step 233, using a Zeta potential analyzer to measure the surface charge state of the treated photovoltaic front panel to confirm that the surface presents a stable negative charge; and / or Step 330 after step 320 includes step 331, observing the formed first M-type coherently arranged structure layer using a scanning electron microscope; step 332, measuring the hydrophobicity of the first M-type coherently arranged structure layer using a contact angle meter. If the contact angle is greater than 90°, it indicates that the hydrophobicity of the first M-type coherently arranged structure layer is good.
11. A method for preparing the anti-dust photovoltaic module according to claim 4 or 5, characterized in that: include: Step A, pre-treating the surface of the photovoltaic front panel and micro-structuring it to form a second M-type coherently arranged structure surface, comprising: Step A1, forming a first wavy microstructure surface with concave and convex surfaces alternately arranged along a first direction, using laser micromachining technology to process the surface of the photovoltaic front panel, arranging multiple laser punching points evenly spaced along the first direction on the surface of the photovoltaic front panel, the spacing between two laser punching points is controlled to be 5~10μm, the punching depth of each laser punching point is controlled to be 1~3μm, and setting the laser power to 15W, the scanning speed to 20mm / s, the repetition frequency to 100kHz, and the energy density to 2J / cm², to obtain the first wavy microstructure surface; Step A2, on the first wavy microstructure surface, change the laser running path to a laser running path perpendicular to the running direction of the laser running path in step A1, repeat step A1, adjust the laser power, the depth is consistent with step A1, on the basis of the first wavy microstructure surface, superimpose the second wavy microstructure surface with alternating concave and convex surfaces arranged along the second direction perpendicular to the first direction, and after smooth round convex points, form the second M-type coherently arranged structure surface.
12. The method for preparing a dust-proof photovoltaic module according to claim 11, characterized in that: Also includes: Step B, preparing a negatively charged nano-coating, comprises: Step B1, preparing a negatively charged nano-coating material, including 5% of nano-hydrophobic SiO2 aerogel, 2% of nano-cellulose, a negatively charged material and an organic solvent, wherein the negatively charged material is 1% of N-doped SnO2, or 0.5% of Ti 4+ 、V 5+ Doped MoO3 or WO3; Step B2, a deposition process, using any one of physical vapor deposition, chemical vapor deposition and plasma vapor deposition techniques to deposit the negatively charged nano-coating material in step B1 on the surface of the photovoltaic front panel treated in step A, controlling the deposition rate to be 0.5 nm / s, and the total deposition time to be 20 minutes, to obtain a conformally deposited negatively charged nano-coating on the surface of the second M-type coherent arrangement structure of the photovoltaic front panel; If N-doped SnO2 is used as the negatively charged material, the deposition process can also adopt ALD atomic layer vapor deposition, replace the gas in the vacuum chamber with a nitrogen-containing gas source, and adjust the negative charge content by adjusting the nitrogen content of the deposited negatively charged material.
13. The method for preparing a dust-proof photovoltaic module according to claim 12, characterized in that: Also includes: Step C, driving the negatively charged nano-coating deposited in step B into the second preset depth on the surface of the second M-shaped coherent arrangement structure of the treated photovoltaic front panel by SE laser technology or plasma etching technology, comprising: Step C1: If SE laser technology is used, set the laser power to 10W, the scanning speed to 10mm / s, the repetition frequency to 50kHz, and the energy density to 1J / cm²; or Step C2: if plasma etching technology is used, argon is used as the working gas, the power is 50 W, and the etching time is 10 minutes.
14. The method for preparing a dust-proof photovoltaic module according to claim 13, characterized in that: It also includes effect verification steps, including: Step A3 after step A2 includes step A31, using a scanning electron microscope to observe the microstructure of the cross section of the photovoltaic front panel to confirm that the surface forms the expected second M-type coherent arrangement structure surface; step A32, using a contact angle meter to measure the contact angle of the photovoltaic front panel surface before and after the treatment to confirm that the increase in surface roughness leads to an increase in the contact angle, indicating that the surface hydrophilicity is reduced; and / or Step B3 after step B2 includes step B31, measuring the thickness of the negatively charged nano-coating by ellipsometry to confirm that the thickness of the negatively charged nano-coating is uniform and the thickness of the negatively charged nano-coating is 300-500 nm; step B32, analyzing the surface of the deposited negatively charged nano-coating by X-ray photoelectron spectroscopy to verify that the coating contains the expected components; and / or Step C3 after step C1 or step C2 includes step C31, using a scanning electron microscope to observe the microstructural changes on the surface of the negatively charged nanocoating to confirm that the negatively charged particles are embedded in the surface of the second M-type coherently arranged structure; step C32, analyzing the surface of the negatively charged nanocoating after treatment by X-ray photoelectron spectroscopy to verify the existence of negative charge centers; step C33, using a Zeta potential analyzer to measure the charge state of the surface of the negatively charged nanocoating after treatment to confirm that the surface presents a stable negative charge.
Citation Information
Patent Citations
Water-based pollution-resistant reflective thermal insulation coating and preparation method thereof
CN106752589A
Preparation method and application of nano coating material for photovoltaic panel
CN115806748A